Work in the Legal System - Vecchio, Giorgio del (1970)
This article deals with the nature and function of work in the Italian legal system. In this context, the article is divided into four parts. First of all, the author makes an approach to the different conceptions of work that have existed throughout history. Secondly, the link between law and labor is developed. In the third part, the author analyzes the problems that symbolize the organization of labor in the State. In this way, the systems that sought to regulate labor are examined, highlighting the influence of trade unionism. The last part focuses on a reflection on work, establishing that it should not be understood only as a social duty, as established in the Italian Constitution, but as a means of expression of the human personality whose purpose is the common good.